Small jellyfish, large consequences: The overlooked predatory role of hydromedusae in subtropical estuarine ecosystems - Guilherme M. von Montfort; Kelly R. Sutherland; Sean Colin; John H. Costello; Renato M. Nagata (Limnology and Oceanography, 2026)
Hydromedusae are often overlooked in pelagic trophic ecology compared to large scyphozoans. We investigated the diet, prey selectivity, ingestion rates, digestion times, and predation impacts of the native Liriope tetraphylla and non‐indigenous species Cnidostoma fallax and Moerisia inkermanica in a subtropical estuary of the southwestern Atlantic. While all three species predominantly consumed copepods, L. tetraphylla exhibited the broadest diet and highest number of preys in gut content (up to 13). Digestion time for L. tetraphylla decreased significantly with increasing temperature, from 94 min at 18°C to 64 min at 28°C, with Q 10 values showing that digestion rates roughly double with a 10°C increase. Cnidostoma fallax exhibited longer digestion times (180 min at 23°C). Daily ingestion rations ranged from 16 to 212 copepods day −1 for L. tetraphylla , 7–15 for C. fallax , and up to 48 for M. inkermanica . Predation impact (PI), the proportion of a prey stock consumed by L. tetraphylla population, averaged 38.1% and peaked at 103.5%, while C. fallax and M. inkermanica had lower impacts (~ 5%). Carbon intake analyses revealed that L. tetraphylla consumed daily up to 280 times its own carbon weight, far exceeding the non‐indigenous species. These results highlight the critical role of hydromedusae in estuarine food webs, challenging the prevailing view that only large gelatinous predators exert top‐down control. We demonstrate that small hydrozoans can be key agents shaping prey community structure and carbon flow in subtropical estuarine ecosystems.

A case of Plasmodium falciparum malaria presenting 13 years after leaving an endemic area - David Hettle; Mustafa Elsayed; Samuel Mensah; Francesca Neuberger; Debbie Nolder; Hristina Vasileva; Kevin Tetteh; Tim Cutfield; Imogen Jones; Spencer Polley; Louise Turner; Thomas Lavstsen; et al. (Infectious Diseases, 2025)

Oceanic lobate ctenophores possess feeding mechanics similar to the impactful coastal species Mnemiopsis leidyi - Malaika Cordeiro; John H. Costello; Brad J. Gemmell; Kelly R. Sutherland; Sean P. Colin (Limnology and Oceanography, 2022)
Lobate ctenophores are often numerically dominant members of oceanic epipelagic and midwater ecosystems. Despite this, little is known about their trophic ecology. Multiple, co‐occurring species are often found in these ecosystems and appear to feed similarly via feeding currents that entrain prey. We quantified the hydrodynamics, morphology, and behavior of four co‐occurring, cosmopolitan lobate species ( Eurhamphaea vexilligera , Ocyropsis crystallina , Bolinopsis vitrea , and Leucothea multicornis ) to evaluate whether their feeding mechanics lead to differential feeding rates and prey selection. We compared the feeding characteristics of these four oceanic species to the coastal lobate ctenophore, Mnemiopsis leidyi , which is known as a voracious zooplanktivore. We found that despite their morphological diversity, the five lobate species used the same mechanism to generate their feeding current—the hydrodynamics of their feeding currents were similarly laminar and with very low fluid deformation rates. Despite having similar feeding current traits, the species had different in situ swimming behaviors and feeding postures. We show that these different behaviors and postures lead to different prey encounter rates and that several of the oceanic species have the potential to feed at rates similar to or greater than M. leidyi . As such, the individual and combined trophic impact of oceanic lobate ctenophores is likely to be much greater than previously predicted.

Centering Indigenous Voices: The Role of Fire in the Boreal Forest of North America - Amy Cardinal Christianson; Colin Robert Sutherland; Faisal Moola; Noémie Gonzalez Bautista; David Young; Heather MacDonald (Current Forestry Reports, 2022)
Purpose of Review Indigenous perspectives have often been overlooked in fire management in North America. With a focus on the boreal region of North America, this paper provides a review of the existing literature documenting Indigenous voices and the historical relationship of Indigenous peoples in northern North America to fire and landscapes that burn. Recent Findings Early research on the topic explored how Indigenous people used fire in the boreal forest, with most research coming out of case studies in northern Alberta. Emerging research in the last two decades has broadened the geographic focus to include case studies in Alaska, Ontario, Labrador, and other regions in North America. This broadening of focus has shown that the diversity of Indigenous peoples in North America is reflected in a diversity of relationships to fire and landscapes that burn. Of note is an emerging interest in Indigenous fire knowledge in the wake of settler colonialism. Summary Indigenous peoples in the boreal forest have applied fire on their landscapes to fulfill numerous objectives for thousands of years. More than a tool, Indigenous peoples in the boreal view fire as an agent, capable of movement, destruction and creation, acting on the landscape to create order, within a living, connected environment. Unfortunately, restrictions on the application of Indigenous fire knowledge and practice initiated during early colonial times remains a contemporary challenge as well.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Four priorities for new links between conservation science and accounting research - Clément Feger; Laurent Mermet; Bhaskar Vira; Prue F.E. Addison; Richard Barker; Frank Birkin; John Burns; Stuart Cooper; Denis Couvet; Thomas Cuckston; Gretchen C. Daily; Colin Dey; et al. (Conservation Biology, 2019)
Article impact statement : New collaborations with accounting research can improve conservation impact of ecosystem‐based information systems.

Resilience in moving water: Effects of turbulence on the predatory impact of the lobate ctenophore Mnemiopsis leidyi - Cornelia Jaspers; John H. Costello; Kelly R. Sutherland; Brad Gemmell; Kelsey N. Lucas; Jennifer Tackett; Kara Dodge; Sean P. Colin (Limnology and Oceanography, 2018)
Despite its delicate morphology, the lobate ctenophore Mnemiopsis leidyi thrives in coastal ecosystems as an influential zooplankton predator. Coastal ecosystems are often characterized as energetic systems with high levels of natural turbulence in the water column. To understand how natural wind‐driven turbulence affects the feeding ecology of M. leidyi , we used a combination of approaches to quantify how naturally and laboratory generated turbulence affects the behavior, feeding processes and feeding impact of M. leidyi . Experiments using laboratory generated turbulence demonstrated that turbulence can reduce M. leidyi feeding rates on copepods and Artemia nauplii by > 50%. However, detailed feeding data from the field, collected during highly variable surface conditions, showed that wind‐driven turbulence did not affect the feeding rates or prey selection of M. leidyi . Additional laboratory experiments and field observations suggest that the feeding process of M. leidyi is resilient to wind‐driven turbulence because M. leidyi shows a behavioral response to turbulence by moving deeper in the water column. Seeking refuge in deeper waters enables M. leidyi to maintain high feeding rates even under high turbulence conditions generated by wind driven mixing. As a result, M. leidyi exerted a consistently high predatory impact on prey populations during highly variable and often energetic wind‐driven mixing conditions. This resilience adds to our understanding of how M. leidyi can thrive in a wide spectrum of environments around the world. The limits to this resilience also set boundaries to its range expansion into novel areas.

Prey capture by the cosmopolitan hydromedusae, Obelia spp., in the viscous regime - Kelly R. Sutherland; Brad J. Gemmell; Sean P. Colin; John H. Costello (Limnology and Oceanography, 2016)

A novel locus for Meckel-Gruber syndrome, MKS3 , maps to chromosome 8q24 - Neil Morgan; Paul Gissen; Saghira Sharif; Laura Baumber; Joan Sutherland; Deirdre Kelly; Kingi Aminu; Christopher Bennett; Geoffrey Woods; Robert Mueller; Richard Trembath; Eamonn Maher; et al. (Human Genetics, 2002)

Nicotine availability from Eclipse tobacco-heating cigarette - J. A. Stapleton; Michael A. H. Russell; Gay Sutherland; Colin Feyerabend (Psychopharmacology, 1998)